Invasive Species in Puerto Rico: The View From El Yunque - Zimmerman, Jess K.; Rojas-Sandoval, Julissa; Shiels, Aaron B. (Frontiers in Ecology and Evolution, 2021)
Native flora and fauna of Puerto Rico have a long biogeographic connection to South America. Theory and empirical evidence suggest that islands, particularly those distantly isolated from the mainland, should be more susceptible to naturalizations and invasions of non-native species than continental areas. Anthropogenic disturbances can facilitate accidental and deliberate introductions of non-native species. In this study, we asked: What is the current status of introduced species within El Yunque National Forest (EYNF), the largest and most well-conserved forest area of Puerto Rico? To address this question, we reviewed the literature and surveyed local experts to identify introduced plant and animal taxa that are behaving as invaders within EYNF. We hypothesized that well-conserved forest areas within EYNF would be more resistant to invasions than disturbed areas along roads and ruderal areas with a long history of human activity. We found that there is only partial evidence that supports our hypothesis and this evidence is strongest in vascular plants, but not for the other taxonomic groups analyzed. Our combined results showed that currently the more ubiquitous invasive species in EYNF include some mammals (feral cat, rat, and mongoose) and some invertebrates (earthworms, mosquito, and Africanized honeybee). For many taxa, there is little information to thoroughly test our hypothesis, and thus more detailed surveys of the status of non-native and invasive species in EYNF are needed.